Futures trading law and regulation in Singapore: an introduction / Margaret Chew Sing Seng - Margaret, Chew Sing Seng (1997)
This paper seeks to be an introductory text and aims to present an overview of the law and regulation of the futures industry and market in Singapore. Chapter 1 begins with a general discussion of the Singapore experience in futures trading, highlighted by the Barings crisis . It continues to chart the objectives of futures trading law and regulation and describes the general framework for supervision of the future market in singapore.